Detecção de Toxoplasma gondii, Neospora caninum, Sarcocystis spp. e Trypanosoma spp. em amostras de cães do Rio Grande do Sul - Ries, Ananda Segabinazzi (2025)
Protozoa can cause systemic disease and central nervous system (CNS) alterations in dogs. Among them, Toxoplasma gondii, Neospora caninum, Sarcocystis spp. (Apicomplexa), and Trypanosoma evansi are of clinical and sanitary relevance. On histopathology, Sarcocystis spp., T. gondii, and N. caninum may exhibit very similar morphology, which hampers distinction without complementary methods. In this context, this thesis combined the molecular investigation of N. caninum, T. gondii, and Sarcocystis spp. in canine brains with the characterization of a T. evansi outbreak in working dogs. In the first study, molecular detection of Apicomplexa was performed in brains from dogs submitted for necropsy at two laboratories in Rio Grande do Sul, Brazil, between 2008 and 2023, organized into two groups: G1 (n = 11), formalin-fixed, paraffin-embedded tissue with a histopathological diagnosis of protozoal encephalitis; and G2 (n = 219), frozen tissue from dogs without a history of neurological disease. DNA was extracted using commercial kits, and all samples were tested by PCR targeting the 18S rRNA gene. In G1 samples, PCR–RFLP was applied to differentiate among the investigated agents. Protozoan DNA was detected in 6/11 G1 samples - two compatible with Neospora caninum, two with Toxoplasma gondii, one with Sarcocystis neurona, and one with Sarcocystis spp. In G2, 82/219 (37.45%) samples were positive, indicating circulation of these agents also in dogs without neurological signs. These findings support the use of complementary techniques such as PCR to confirm the etiology and reduce diagnostic uncertainty when morphology is similar, and also highlight the circulation of these agents in animals without neurological signs. In the second study, an outbreak of Trypanosoma evansi was investigated in 34 dogs used in wild boar management. The animals underwent clinical examination, complete blood count, parasitological detection in blood smears, PCR and serology for Trypanosoma spp.; parasitological detection was observed in eight dogs, molecular confirmation in six, and no seropositive animals were identified. Two dogs died and were necropsied. The set of epidemiological evidence from the outbreak (direct exposure to blood and viscera during handling, with temporal clustering of cases), together with precedents of oral transmission in dogs, is consistent with infection through ingestion of blood and/or tissues from infected wild boar. Of the 34 dogs treated with diminazene aceturate, 18 improved after the first administration; the remaining 14 received a second dose, after which 10 improved and four died. This study underscores the need to include T. evansi in the diagnostic work-up of working dogs exposed during wildlife management and to adopt preventive measures to reduce transmission risk. The studies in this thesis demonstrate that: (i) PCR targeting 18S rRNA in brain tissue, together with PCR–RFLP, assists etiologic confirmation of T. gondii, N. caninum, and Sarcocystis spp.; (ii) these agents are also detected in dogs without a history of neurological signs; (iii) dogs used in wild boar management can become infected by T. evansi, with clinical and pathological impact; and (iv) incorporating these protozoa into the differential diagnosis of canine CNS diseases, and implementing surveillance and preventive actions, are necessary measures aligned with the One Health perspective.